2022
DOI: 10.3390/su14095306
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Seasonal Phytoplankton Pigments and Functional Types around Offshore Island in the East/Japan Sea, Based on HPLC Pigment Analysis

Abstract: In this study, we investigated the seasonal phytoplankton community and phytoplankton functional types (PFTs) in the vicinity of Dokdo Island, located in the East/Japan Sea, in 2019. With strong seasonal winds, the water column was well mixed in winter. In spring and autumn, the upper mixed layer depth (MLD) was relatively deep, and the Subsurface Chlorophyll Maximum (SCM) formed in the middle layer. Small phytoplankton were dominant in the summer, which is a time of high water temperatures and strong stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…However, previous studies on phytoplankton communities in the East Sea reported differences in the dominant communities depending on the study period and survey station [41][42][43][44][45]. An observation shared among most of these studies is that the size of the key dominant size of the phytoplankton communities tends to decrease as the water temperature increases after spring [41,[43][44][45]. According to the observations of phytoplankton communities in the South Sea and East China Sea from January to May, micro-size phytoplankton are dominant in the west, whereas pico-size phytoplankton are dominant in the central region.…”
Section: Estimation Of Phytoplankton Size Classes In the Littoral Sea...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, previous studies on phytoplankton communities in the East Sea reported differences in the dominant communities depending on the study period and survey station [41][42][43][44][45]. An observation shared among most of these studies is that the size of the key dominant size of the phytoplankton communities tends to decrease as the water temperature increases after spring [41,[43][44][45]. According to the observations of phytoplankton communities in the South Sea and East China Sea from January to May, micro-size phytoplankton are dominant in the west, whereas pico-size phytoplankton are dominant in the central region.…”
Section: Estimation Of Phytoplankton Size Classes In the Littoral Sea...mentioning
confidence: 95%
“…According to prior research, the key dominant size of phytoplankton communities in spring (March-April) in the East Sea are micro-size diatoms [38][39][40]. However, previous studies on phytoplankton communities in the East Sea reported differences in the dominant communities depending on the study period and survey station [41][42][43][44][45]. An observation shared among most of these studies is that the size of the key dominant size of the phytoplankton communities tends to decrease as the water temperature increases after spring [41,[43][44][45].…”
Section: Estimation Of Phytoplankton Size Classes In the Littoral Sea...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Korea Institute of Ocean Science and Technology (KIOST) has been conducting studies in the Ulleung Basin, including Ulleungdo and Dokdo, as a hub for systematic research in marine physics, chemistry, and biology since 2000. While some studies have explored the response of phytoplankton to physical characteristics in the Ulleung Basin [8,15,16], as well as phytoplankton population dynamics and photosynthetic pigments around Ulleungdo and Dokdo [17][18][19], most of these investigations have been limited to short-term studies, and there has been a lack of periodic research centered around Dokdo. However, it is not easily accessible and is subject to the influences of weather and wave conditions that can change rapidly in the waters around Dokdo due to its unique geographical and oceanographic attributes.…”
Section: Introductionmentioning
confidence: 99%
“…The average water depth of the East Sea is 1700 m, but it has deep basins exceeding 2500 m in depth. The East Sea has a well-defined sub-polar front at approximately 37-40 • N [7]. This front is created between a warm water mass from the East Korea Warm Current (EKWC), which branches from the Tsushima Warm Current (TWC), and a cold water mass from the North Korea Cold Current (NKCC), a branch of the Liman Current.…”
Section: Introductionmentioning
confidence: 99%